Antioxidant and cytotoxic lignans from the roots of Bupleurum chinense. Issue 5 (4th May 2017) - Li, Dan-Qi; Wang, Di; Zhou, Le; Li, Ling-Zhi; Liu, Qing-Bo; Wu, Ying-Ying; Yang, Jing-Yu; Song, Shao-Jiang; Wu, Chun-Fu
Abstract: In the search for biologically active compounds from the roots of Bupleurum chinense D C., phytochemical investigation of its ethanol extract led to the isolation and identification of a new 8- O -4′ neolignan glucoside, saikolignanoside A (1 ), along with eight known lignans (2–9 ). Their structures were determined on the basis of IR, UV, HRESIMS, and NMR spectroscopic analyses. The antioxidant and cytotoxic effects of isolated compounds were evaluated in vitro . The isolated compounds (IC50 > 200 μM) did not display 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity. Whereas compounds1–2, 5, 7, and9 exhibited potent 2, 2′-azinobis(3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS) free radical scavenging properties with IC50 values ranging from 8.34 to 15.24 μM, while compounds3–4, 6, 8 showed moderate properties. In addition, all compounds were evaluated for cytotoxicities against A549, HepG2, U251, Bcap-37, and MCF-7 cell lines. Compounds5 and9 (IC50 < 51.62 μM) possessed stronger cytotoxic activities against all the tested tumor cell lines, compared with the positive control 5-Fluorouracil.